Outcomes of 157 V-Patch™ Implants in the Repair of Umbilical, Epigastric, and Incisional Hernias. Issue 1 (January 2016) - Keating, Jane J.; Kennedy, Gregory T.; Datta, Jashodeep; Schuricht, Alan
Umbilical, epigastric, and incisional hernias have traditionally been repaired using a Mayo or tensioned suture technique, with recurrence rates of approximately 50 per cent. Recent studies have shown that a tension-free repair using mesh can drastically decrease recurrence rates. Reinforced deployment prostheses are preferred because they enable retrofascial placement through a small incision, thus avoiding the potential morbidity of a larger incision and the costs associated with a laparoscopic approach. A retrospective chart review was performed of all umbilical, epigastric and incisional hernias repaired with V-Patch, a reinforced deployment prosthesis, by a single surgeon. Data analysis included patient characteristics, operative and postoperative metrics, hernia recurrence, and complication rates. Between 2009 and 2012, 157 implantations were performed in 152 patients during 156 procedures. Patient age ranged from 20 to 85 (mean 48). There were 88 females (57.9%) and 64 males (42.1%) with average body mass index of 30.6. Patch size distribution was 78 small (49.7%), 55 medium (35.0%), and 24 large (15.3%). There were 81 umbilical hernias (51.6%), 36 epigastric hernias (22.9%), 39 incisional hernias (24.8%), and 1 multiple recurrent inguinal hernia (0.6%) repaired. Follow-up time ranged from 18 months to 4.3 years. There were six hernia recurrences (3.2%). Complications included three patients (1.9%) with mesh infection, one with an enterocutaneous fistula (0.6%), and one patient with a postoperative small bowel obstruction (0.6%). Four patients required patch explantation (2.5%). The V-Patch reinforced deployment prosthesis is effective in the treatment of umbilical, epigastric, and incisional hernias, and has a low rate of complications.